VALUE CO-CREATION AND PRODUCT DIFFERENTIATION IN THE CREATIVE ECONOMY: INSIGHTS FOR GAINING COMPETITIVE ADVANTAGE A COMPREHENSIVE REVIEW - Putri, Nadira Ruri Kusuma; Hardjono, Retno Kusumastuti (Universitas Muhammadiyah Metro Lampung, 2023)
The purpose of this study is to determine the value in business, how competitive advantage through differentiated products, and competitive advantage can affect the value creation process.This research uses literature review metod. The results showed that value co-creation has a positive impact on competitive advantage, as well as differentiation which has a positive effect on competitive advantage because it is necessary to diversify products in accordance with customer tastes and current consumer needs. This research extends existing thinking about value networks and value creation. The novelty of this study lies in the development and empirical testing of Prahalad's (2004) five activities to provide a comprehensive set of activities that represent value creation, i.e. Joint reflection and joint recovery are proposed for the first time to capture various dimensions of value creation. dimensions of value creation. The findings support the positive impact of partner engagement, joint reflection, and joint problem solving after a service failure.This research provides guidance for management practices in creative industries that want to develop their capabilities and deliver superior value. It is expected that craftsmen are able to increase awareness of creating new ideas by changing or implementing existing ideas in new ways. Competitive advantage is the extent to which creative industry players can obtain and maintain a position of advantage over their competitors through the creation of value for their customers.Keywords: Value Co-Creation, Product Differentiation, Competitive Advantage